Full 4‐port deembedding of differential transmission line interfaces by 2‐port reflection measurements with mode conversion excitation. Issue 8 (1st April 2017) - Ritter, P.; Möller, M.
Abstract : An approach is presented for the determination of the 4 × 4 transmission matrix of differential transmission line interfaces on a microchip fixture. Different settings of a simple calibration structure that extends the already available 50‐Ω on‐chip termination excite different transmission modes, which are used for the determination of the transmission matrix in mixed mode parameter form. Only reflection measurements at the two easily accessible connectors of the fixture are required, which enables an in‐situ deembedding of the chip performance while mounted.